The influence of organisational behaviour, inclusive work environment, and career development on the performance of gen z employees with work engagement as a moderating variable - Cawla, Meylie; Suhardi, Suhardi; Hamdan, Hamdan; Yani, Ahmad (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
This study aims to analyze the influence of organizational behavior, inclusive work environment, and career development on the performance of Gen Z employees in Indonesia, with work engagement as an intervening variable. Given Gen Z's dominance in the modern workforce, understanding the factors that drive their productivity is crucial. The research method used was a quantitative explanatory method with a survey technique through a questionnaire to 111 Gen Z employee respondents. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) to test the structural relationships between variables as well as the moderating and mediating effects. The results show that an inclusive work environment is the most significant driver of work engagement, which then has a positive impact on improving employee performance. Career development has a positive effect, but on a smaller scale. In contrast, organizational behavior does not show a significant influence on work engagement or performance in the context of this study's respondents. These findings confirm that work engagement is a key variable that transforms organizational resources into tangible performance. Therefore, organizations are advised to prioritize the creation of an inclusive work climate to optimize the potential of young employees.